2020
DOI: 10.3390/jof6040210
|View full text |Cite
|
Sign up to set email alerts
|

Fungus Aspergillus niger Processes Exogenous Zinc Nanoparticles into a Biogenic Oxalate Mineral

Abstract: Zinc oxide nanoparticles (ZnO NPs) belong to the most widely used nanoparticles in both commercial products and industrial applications. Hence, they are frequently released into the environment. Soil fungi can affect the mobilization of zinc from ZnO NPs in soils, and thus they can heavily influence the mobility and bioavailability of zinc there. Therefore, ubiquitous soil fungus Aspergillus niger was selected as a test organism to evaluate the fungal interaction with ZnO NPs. As anticipated, the A. niger stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…As a result, Aspergillus niger, a common soil fungus, was chosen as a test organism to evaluate fungal interactions with ZnO NPs. As expected, the A. niger strain had a significant effect on the stability of particulate forms of ZnO due to the acidification of its environment [15]. The macrofungi-derived NPs produced by major mushroom species such as Agaricus bisporus, Pleurotus spp., Lentinus spp.…”
Section: Introductionsupporting
confidence: 61%
“…As a result, Aspergillus niger, a common soil fungus, was chosen as a test organism to evaluate fungal interactions with ZnO NPs. As expected, the A. niger strain had a significant effect on the stability of particulate forms of ZnO due to the acidification of its environment [15]. The macrofungi-derived NPs produced by major mushroom species such as Agaricus bisporus, Pleurotus spp., Lentinus spp.…”
Section: Introductionsupporting
confidence: 61%
“…The chitin/ZnO composites showed antibacterial properties against Gram-positive bacteria [ 52 ]. In another work, extracellular metabolites of A. niger were used to transform ZnO-NPs into a zinc oxalate [ 53 ]. The results show that due to the presence of high active metabolites, A. niger can biomineralize inorganic NPs and transform these NPs into more stable oxalate complexes.…”
Section: Resultsmentioning
confidence: 99%
“…In intracellular synthesis, transportation of metal ions within the cell takes place where they are reduced by enzymes present there which leads to increase in nuclei resulting in nanoparticles formation in the periplasmic space and cytoplasm [39]. Mukherjee et al [42] reported intracellular mechanism for NPs by Verticillium sp. Consisting of three steps trapping, bioreduction and capping.…”
Section: Biofabrication By Using Fungimentioning
confidence: 99%
“…Cell filtrate of this both fungal strain was treated with 2mM zinc acetate [Zn(CH3CO2)2] to form precipitate which was dried at 150˚C for 48h to be used for further investigation [45]. Identical method was used for the synthesis of ZnO NPs by using zinc nitrate hexahydrate [Zn (NO3)2.6H2O] with fungal filtrate of Xylaria acuta followed by heating the reaction mixture [42].…”
Section: Biofabrication By Using Fungimentioning
confidence: 99%